Library services for visually impaired persons in Malaysia / Pak Say Wah - Pak , Say Wah (2007)
Library services for visually impaired persons (VIPs) play an important role in providing for their information needs. This study describes the current status of library services for VIPs in Malaysia. It provides information that could be useful for the improvement of library services for VIPs in this country. Questionnaires were sent to 16 public libraries (National and State) and 2 special libraries for VIPs. A 100% response rate was achieved. The key issues studied were the provision of library materials, equipment and services, and the management of the libraries. It was found that the level of provision of each type of library material studied was rather low, with more libraries not having provision compared to libraries with provision. For each type of library equipment studied, not more than one third of the libraries provided them. The services and management related to provisions for VIPs were also lacking. Only eight out of the eighteen libraries were found to have provision of library services for VIPs and were targeting VIPs as a user group. The problems and facilitating factors that affected this provision were studied. The problem most frequently faced by libraries with provision was getting in touch with visually impaired potential users. The initiative of the library directors was the most frequently mentioned factor that facilitated the provision of services for VIPs. For libraries without provision of library services for VIPs, the main factor that hindered this provision was the lack of funds. Recommendations for improvements are provided in this report.